Scaling-up Higher Order Thinking Demonstrating a Paradigm for Deep Educational Change - Zohar, Anat (Springer Nature, 2023)
This open access book addresses the evasive problem of why truly effective educational innovation on a wide scale is so difficult to achieve, and what leaders may do about this. Examining the case of system-wide reform processes centering on teaching a thinking-rich curriculum, it discusses general issues pertaining to implementing deep, large-scale changes in the core of learning and instruction. The book emphasizes challenges related to professional development, assessment, achievement gaps, and the tension between knowledge and skills in 21st century curricula. It summarizes insights the author has gained from approximately 25 years of engaging with these topics both as an academic and as a practitioner who led a national change process. With a Forward by David Perkins